Dialectic of Humanity and Nationality in Uzbek EthnoCulture - Umid Menglikulov (Zien Journals, 2022)
The article puts forth the idea that universality and nationalism in the ethnic culture of the Uzbek people are dialectically related and a phenomenon formed in the course of a long socio-historical development. There are also further information and comments on the concepts of ethnic culture, sub-ethnic culture, tradition, custom, and ceremony.
Keywords: culture; ethnic culture; value; custom